KOALISI PARTAI DEMOKRASI INDONESIA PERJUANGAN- PARTAI KEBANGKITAN BANGSA-PARTAI AMANAT NASIONAL DAN PARTAI KEADILAN SEJAHTERA DALAM PEMILIHAN KEPALA DAERAH KABUPATEN PURBALINGGA TAHUN 2010 - Khanif Idris; Fitriyah .; Muhammad Adnan (Journal of Politic and Government Studies, 2014)
Some researches about coalition had done by scholars show us the unstructured pattern of party coalition among one area to others. One of them is the research by Riri Romly which said that coalition among parties in a direct local election is pragmatic coalition. It is a kind of coalition which neglects the similarity of ideology, vision and mission, platform, and also working programs. Unfortunately it also happened in the coalition which is support the winner of Regent Election in Purbalingga, Central Java where PDI Perjuangan as the winner of legislative election there, develops coalition with PKB, PKS, and PAN which is near with Moslem society. In this research, the author wants to know what the reasons of that coalition are. Besides, it also can be additional reference for coalition among political parties. In other hand, to do this research, the author use qualitative method and the data collection methods are interview and documentary study. Those data which I got, then, ascertained its validity by triangulation method, especially Method Triangulation. From those background and research method, the result of this research is the author got the fact which shows us that the coalition among them only based on the aim to be winner by embrace every element in the society, the nationalist and the religious (Moslem). All in all, this result is in line with Heywood though which said that one of the motifs of coalition among parties is to win the game or called as Electoral Coalition.